The Influence of the System of Physical Education of Higher Educational School on the Level of Psychophysiological Qualities of Young People - Volodymyr Klymovych; Mukola Korchagin; Oleh Olkhovyі; Serhii Romanchuk; Artur Oderov (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
In terms of functioning of physical education system in higher educational establishments, a four-year educational pedagogical experiment with the application of the directional technology of acquiring professional-applied motor skills was implemented. According to the results of approbation of experimental technology, a reliable improvement in the state of psychophysiological qualities was recorded in the study group: evaluation of the process of main nervous processes excitation - by 125.32 Ms (p<0.001), the forces of the excitation process, internal inhibition and mobility of the main nervous processes - by 145.99 Ms (p<0.001), "an adequate indicator of the relative change in the strength of the excitation process, internal inhibition and mobility of the main nervous processes" - by 20.66 Ms (p<0.001).